STUDENTS’ VISIONS OF HAPPINESS - V. G. Petrov; K. V. Zlygosteva (Вестник Кемеровского государственного университета, 2015)
The paper deals with the problem of modern students‘ visions of happiness. The authors propose a conceptual model of visions of happiness. According to the authors, the vision of happiness is a complex cognitive structure, which belongs to the category of implicit (internal) and social (cultural and historical) representations, defining the person‘s attitude to happiness, the ability to perceive it, awareness and experience. The paper shows that the average level of happiness prevails among students. Problems were identified in the research for most indicators: some indicators of vitality, irrational аttitudes, indicators of the scale of existence have a low degree of expression. Correlation analysis showed that the perceived happiness is interconnected with a high degree of life satisfaction and subjective well-being; with vitality, with the absence of irrational attitudes, with the absence of irrational settings, with high values on the scale of existence. This problem continues to be developed, taking into account a variety of factors: age, gender, cultural, ethnic, social, etc.